Control of mango anthracnose by hot water and fungicides treatment - B. K. PANDEY, OM PRAKASH and (Indian Phytopathology, 2002)
Following harvest, mango (cv. Dashehari) fruits were treated with hot water at 52â„ƒ for 5, 15 and 30 min alone and in combination with fungicides to control postharvest anthracnose (Colletotrichum gloeosporioides [Glomerella cingulata]) disease. Hotwater (52â„ƒ) alone for 30 min was very effective in controlling the disease. Treated fruits could be stored at 12?for up to 26 days (21 days at 12?+ 5 days at ambient temperature for ripening). However, the duration of hot water treatment could be reduced to 15 min by supplementing with carbendazim or thiophanate-methyl (each @ 0.1%). Hot water (52?for 15 min) together with carbendazim treated fruits could be stored for 26 days at 12?without any anthracnose infection, while with thiophanate-methylfruits could be stored for only 19 days at 12? Fungicides applied at ambient temperature did not control anthracnose. Hot water treatments did not show any adverse effect on fruit ripening.